Discourse markers in non-native EFL teacher talk - Vickov, Gloria; Jakupčević, Eva (Studies in Second Language Learning and Teaching, 2017)
The present study aims to investigate the use of discourse markers (DMs) in non-native (Croatian) EFL teachers´ talk with primary and secondary school students. The study concentrates on the occurrences and frequencies of DMs, but it also provides an account of the function distribution of the three most frequently used DMs (ok, so, and). The quantitative and qualitative analyses of the recorded transcriptions reveal that the teachers use a variety of DMs, almost exclusively the ones typical of classroom management and classroom discourse organization, with no significant differences in the patterns of DM use with the primary and secondary school students. The DMs fulfill a number of structural and interpersonal functions mainly aimed at providing coherent and stimulating classroom discourse. The findings of this study might contribute to raising awareness of the diversified functions of DMs, which could facilitate non-native EFL teachers´ overall lesson organization and structuring of particular teaching segments.